KEBERHASILAN SVLK DALAM MENDUKUNG PERBAIKAN TATA KELOLA KEHUTANAN - Yuli Miniarti; Yuki M.A. Wardhana; Chairil Abdini (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2018)
The Timber Legality Verification System (SVLK) is an instrument stipulated by the Government of Indonesia to build legitimacy on Indonesian forestry governance policies, especially those related to the utilization and distribution of timber forest products. The objective of SVLK is to cut the supply chain of illegal timber from the forest management unit to the market, through timber legality assurance. Since the enactment of SVLK in 2009, there has been no evaluation of the SVLK policy to measure its effectiveness. This study aimed to evaluate the success of SVLK in supporting the improvement of forestry governance. The analytical method used by this study is a descriptive formal evaluation. Interviews were conducted to representatives of four related stakeholder groups: six persons from timber forest product associations, five persons from three government agencies, one person from NGO, and one person from academia. The results of the study indicated that SVLK policy has quite successfully supported the improvement of forestry governance. In this regard, improvement is figured as 46% of law enforcement, 45% of accountability, 43% of participation, 42% of transparency, and 31% of coordination. It can be concluded that the SVLK policy has been quite successful in improving foresty governance.